2021
DOI: 10.1037/bul0000342
|View full text |Cite
|
Sign up to set email alerts
|

Development of relationship satisfaction across the life span: A systematic review and meta-analysis.

Abstract: Previous research has not led to any agreement as to the normative trajectory of relationship satisfaction. In this systematic review and meta-analysis, we summarize the available evidence on development of relationship satisfaction, as a function of age and relationship duration. Data came from 165 independent samples including 165,039 participants. In the analyses, we examined cross-sectional information on mean level, that is, the percent-of-maximum-possible (POMP) score at the first assessment, and longitu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
86
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 251 publications
(416 reference statements)
11
86
0
Order By: Relevance
“…In other words, the younger cohort's relationships seemed to be resistant to the negative impact of most proximal forms of minority stressor. Members of the younger cohort were also more satisfied with their relationships in general than were members of the older cohorts; a finding which parallels research on age and relationship satisfaction in the general population (Bühler et al, 2021).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In other words, the younger cohort's relationships seemed to be resistant to the negative impact of most proximal forms of minority stressor. Members of the younger cohort were also more satisfied with their relationships in general than were members of the older cohorts; a finding which parallels research on age and relationship satisfaction in the general population (Bühler et al, 2021).…”
Section: Discussionsupporting
confidence: 71%
“…An investigation into the ways in which minority stress impacts the quality of relationships of different cohorts of sexual minority individuals requires contextualization within other developmental and life course influences on romantic relationships. Theory and research (for a review and meta-analysis, see Bühler et al, 2021) have identified age and length of relationship as two important factors influencing relationship quality (i.e., satisfaction) that require consideration in our focus on cohort differences in the association between minority stress and relationship quality. Meta-analyses of the role of age indicated that mean levels of relationship satisfaction tend to be highest in early adulthood and decrease sharply from age 20 to 30, while findings on relationship duration indicate satisfaction is at its highest level at the start of relationships followed by a steep decline in satisfaction over the first 10 years (Bühler et al, 2021).…”
Section: Additional Developmental and Life Course Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies focusing on positive relationship functioning in people with diverse sexual orientations yield mixed results, with evidence for negative (Sommantico et al, 2019(Sommantico et al, , 2020, positive (Vale & Bisconti, 2021), no (Pepping et al, 2019) or differential (Totenhagen et al, 2018) associations with age and no (Rice et al, 2020;Vale & Bisconti, 2021) or differential (Totenhagen et al, 2018) associations with relationship length. This is not surprising, as a recent meta-analysis with studies from the general (i.e., presumably mostly heterosexual) population found evidence for non-linear relations between relationship satisfaction and age and relationship length respectively (Bühler et al, 2021). Thus, our cross-sectional design does not allow for a more nuanced understanding of the longitudinal associations between these variables.…”
Section: Discussionmentioning
confidence: 77%
“…First, we predicted that the German-version of the LGB-PIM would show acceptable model fit (Hypothesis 1). Second, we predicted positive associations between the five positive minority identity aspects (i.e., self-awareness, authenticity, community, intimacy, social justice) in people with diverse sexual orientations and their self-reported relationship quality, after controlling for relevant confounds, namely age (Baiocco et al, 2020;Bühler et al, 2021), gender identity (Marshall et al, 2020;Sommantico et al, 2019Sommantico et al, , 2020Song et al, 2021), sexual orientation (or couple gender in a sensitivity analysis; Baiocco et al, 2020;Morandini et al, 2018), relationship length (Bühler et al, 2021), and psychological distress (Braithwaite & Holt-Lunstad, 2017;Riggle et al, 2014;Hypothesis 2).…”
Section: The Present Studymentioning
confidence: 92%